Studi Komparatif Terkait Kompetensi Guru di Negara Finlandia dan Indonesia - Septy Widyorini; Vika widiana Lestari; Taufik Muhtarom (STIKes Ibnu Sina Ajibarang, 2024)
: Etymologically, comparative education means comparing two or more educational systems and studying procedures or procedures. It is not surprising that the term